From Brain to Body: The Impact of Nervous System Declines on Muscle Performance in Aging - Brian C. Clark (Frontiers Research Topics, 2015)
The deterioration of skeletal muscle performance (e.g., declines in muscle strength and motor performance) with advancing age has long been anecdotally recognized as Shakespeare pointed out nearly a half millennium ago in his monologue The Seven Ages of Man, and has been of scientific interest for well over a century. Over the past several decades the scientific and medical communities have recognized that reduced skeletal muscle performance is a debilitating and life threatening condition in the elderly. For example, the age-associated loss of muscle strength, as well as impairment in the ability to finely control movement, is highly associated with physical disability and difficulty performing activities of daily living. While the nervous system is widely recognized for its role in controlling skeletal muscle during motor function, its role in determining the performance characteristics of aged skeletal muscle has largely been understudied. Historically, it was believed that these reductions in muscle performance were primarily resultant of age-associated adaptations in skeletal muscle (e.g., muscle atrophy). However, aging is associated with widespread qualitative and quantitative changes in both the central and peripheral nervous systems that are likely to influence numerous aspects of muscle performance, such as muscle strength, fatigue, and motor control, as well as mobility. In this research topic, we sought to examine a broad range of issues surrounding: 1) the age-related changes in nervous system anatomical, physiological, and biochemical changes in the central and/or peripheral nervous systems; 2) the functional role of these nervous system changes in contributing to altered skeletal muscle performance and/or mobility; and 3) physical and pharmacologic interventions that act via the nervous system to enhance muscle performance and/or mobility. Researchers and academicians engaged in aging, neuroscience, and/or applied physiology research focused within the scope of this research topic, were encouraged to contribute an original research article, review article, clinical case study, hypothesis and theory article, method article, opinion article, or technology report to this research topic. Herein, we present a series of outstanding articles within this scope of work, including a last minute addition article from Wiesmeier, Dalin and Maurer that is not mentioned in the editorial, that we hope will help to vertically advance the intersecting fields of aging/geriatrics and neuroscience. Lastly, as the editors, we wish to thank all article contributors and peer reviewers for their efforts in contributing to this Research Topic journal issue/book. Additionally, we would like to thank people everywhere who volunteer their time and body for human subjects research studies, such that are presented herein. It is the wonderful individuals who are willing to participate in experiments that make scientific exploration and health and medical advancements possible.